Quality provision in Pakistani health care system: insights into a major obstacle and the way forward - Hamza Khan,; Javed Ahmed Chandio,; Atif Bilal Shoaib, (Journal of the Pakistan Medical Association, 2023)
Madam, Safety, cost-effectiveness, efficiency and equity are all components of quality healthcare. Key factors determining quality are’ and their families’ satisfactions and better disease outcomes.1 Doctors, paramedics, pharmacists, laboratory technicians, administrative staff, pharmaceutical companies, government agencies and policymakers are the caregivers who have an essential direct or indirect role in providing, sustaining and improving health care.1 A population's health is crucial to a state's stability and growth. Quality in healthcare has been a subject of discussion across the globe for decades, with developed nations contributing the majority of its measures and recommendations6. In contrast it is still battling to fully establish and function in emerging nations like Pakistan. The health system in Pakistan comprises primary, secondary and tertiary health centres. The latter are found in a few urban cities and are run by both the public and private sectors. Private bodies include profit as well as welfare-based organizations.2,3 According to the WHO, on average, there are 6.3 hospital beds per 10,000 population in Pakistan, which is below its recommendation and much less compared to other developing nations.2 Majority of the population reside in rural areas and thus their option in various illnesses is primary or secondary health unit.3 The major drawback in such centres is lack of attendance by doctors and paramedical staff, lack of competent clinician or general practitioner along with absence of equipment, state-of-the-art laboratory and latest treatment options, all contributing to delays in diagnosis and management.4,5 There is also a lack of patient registry, long-term follow-ups, appropriate and timely referrals to higher health care centre and disease discussion between clinicians.3 Due to such weakened basic units, many patients directly visit an urbanized tertiary health center, which is a major cause of overcrowding of our hospitals. Some break-through policies which could address this dilemma is giving incentives to the assigned staff, providing commute in case of long travels, improving the infrastructure and facilities within the centers, installation of biometrics and having regular audit of attendance, number of patients treated and medications provided. Conducting education seminars regarding work ethics would also contribute towards a professional working environment leading to better patient outcomes.3,4 Creating awareness regarding the responsibility and crucial role of general practitioners in primary and secondary health units along with recognition of their importance, would also help in diverting medical community towards opting for such roles.6 ---Continue